Optimalisasi Proses Penanganan Penumpukan Batupack untuk Mengurangi Pemborosan di Industri Batubara melalui Pendekatan Value Stream Mapping (VSM) - Berry Eka Putra; Putri Endah Suwarni; Dita Meliana; Susanti Sundari (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
The batupack handling process still experiences waste that results in prolonged processing time, excessive fuel consumption, and increased operational downtime. This study aims to identify the sources of waste, analyze their root causes, and evaluate process efficiency using the Lean Manufacturing approach through Value Stream Mapping, Process Activity Mapping, VALSAT, and Fishbone Diagram. The findings indicate that the dominant types of waste are transportation, waiting, and motion. The proposed improvements successfully reduced the cycle time from 313 minutes to 130 minutes and the lead time from 468 minutes to 153 minutes, increased Value Added activities from 20% to 78.4%, and reduced Non-Value Added activities from 41% to 2%. In addition, the improvements decreased operational downtime from 23.17 hours to 1.83 hours per month, reduced diesel fuel consumption from 4,716.61 liters to 1,061.23 liters per year, increased production potential by 85,360 tons annually with an additional profit of IDR 94.49 billion, and lowered CO₂, SOx, and NO₂ emissions. These findings demonstrate that the proposed approach effectively improves operational efficiency while supporting the sustainability of the material handling process. Keywords: Fishbone Diagram, Lean Manufacturin, Process Activity Mapping, VALSAT,  Value Stream Mapping, Waste.